Performa Anak Domba Prolifik Diberi Susu Pengganti Mengandung Pepton Asal Ikan Kembung (Rastrelliger sp.): Performance of Prolific Lambs Fed by Milk Replacer Containing Peptone of Mackerel (Rastrelliger sp.) - Manik, Btr Sri Syntia; wijayanti, indah; khotijah, lilis; nurhayati, Tati (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
The purpose of this study was to evaluate the performance of prolific lambs fed milk replacer derived from mackerel peptone with prolific lambs fed mother’s milk. This study used six twin born lambs aged 1 week with an average birth weight of ± 2.05 kg and male. The treatments applied in this study were mother’s milk (P0) and milk replacer containing 100% mackerel peptone (P1). The observed variables included ash content, crude protein content, crude fat content, calcium content, phosphorus content, total nitrogen, total volatile base (TVB) content, milk amino acid profile, milk consumption, body weight gain, feed conversion rate, and mortality. The results showed that milk replacer containing 100% mackerel peptone had high crude protein content and complete amino acid composition. Prolific lambs fed with milk replacers showed no significant difference in body weight gain compared to those suckling from their mothers. Additionally, lambs receiving the milk replacer did not exhibit any signs of digestive disorders, loss of appetite, abnormal behavior, or mortality during the maintenance period. Utilization of mackerel peptone as an alternative protein source can be used up to 100% in milk replacer. It can be concluded that feeding milk replacers formulated with mackerel peptone resulted in a 1.30% increase in lamb body weight, with no significant difference observed in performance compared to lambs suckling form their mothers. Key words: lamb, milk replacer, peptone, prolific, protein